Cost Reduction and Efficiency Boost Through E-Commerce Strategies: Pengurangan Biaya dan Peningkatan Efisiensi Melalui Strategi E-Commerce - Jawad, Shejn Ghalib; Mohammed, Abbas Hazim (Indonesian Journal of Law and Economics Review, 2024)
General Background: E-commerce has revolutionized business practices by offering cost reduction, especially in marketing, through advancements in electronics and communication, expanding reach, and reducing operational costs. Specific Background: This study investigates the potential of e-commerce in reducing marketing costs and improving business efficiency, despite challenges faced by many firms. Knowledge Gap: While extensive research exists on e-commerce, the specific relationship between e-commerce strategies and the reduction of promotional costs remains underexplored, especially in terms of practical implementation by companies. Aims: The study explores the link between e-commerce strategies and reduced promotional expenses, highlighting how digital marketing can boost profitability and reduce costs for businesses. Results: Statistical analysis revealed that companies effectively reduced advertising costs, such as salaries, bonuses, and training expenses, by utilizing e-commerce strategies. However, many firms failed to capitalize on further cost-saving opportunities in inventory management, travel, and research expenses. The t-value (17.062) and p-value (0.000) indicate a significant relationship between e-commerce strategies and reduced promotional costs. Novelty: This research provides empirical evidence on the significant cost-saving potential of e-commerce, highlighting its underutilization in areas beyond marketing, such as operational expenses. Implications: The study emphasizes the importance of integrating e-commerce into operational strategies for cost reduction and competitive pricing, providing practical insights for businesses aiming to improve efficiency and profitability. Highlights: E-commerce reduces marketing costs and boosts business efficiency. Firms often miss broader cost-saving potential of e-commerce. Strong correlation found between e-commerce use and lower promotional expenses. Keywords: E-commerce, digital marketing, cost reduction, promotional expenses, business efficiency